VENTRİKÜLOATRİAL ŞANTLAMA: YATAĞA BAĞIMLI HİDROSEFALİLİ HASTALARDA ALTERNATİF BİR TEDAVİ SEÇENEĞİ - CANBAZ, Bülent; ULU, Mustafa Onur; TANRIVERDİ, Taner; TÜZGEN, Saffet; İŞLER, Cihan; KAYNAR, Mehmet Yaşar (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Treatment of hydrocephalus in some patients is one of the most challenging problems encountered in neurosurgical practice and ventriculoperitoneal (VP) and ventriculoatrial (VA) shunting are the two most popular surgical treatment modalities. VP shunting, although having less serious complications than VA shunting, may not function properly due to the increased intraabdominal pressure in a particular group of bedridden patients and require revisions. VA shunting, on the other hand, due to its severe and life-threatening complications are performed less commonly since 1950’s. However, clinical experiences support the opinion that VA shunting may be an ideal treatment modality for bedridden patients with hydrocephalus and the purpose of this study was to evaluate our experiences in this particular group of patients. This prospective study includes 10 bedridden patients (F/M=6/4) with hydrocephalus, who underwent VA shunting operation in the Neurosurgery Department of Cerrahpasa Medical Faculty between May 2002-May 2003.The clinical outcome was obtained from the hospital charts and the results were compared. Results.- Two patients were dead during the follow up period. One patient was lost due to sepsis and the other one died because of unrelated causes. The rest of the patients had clearly benefited from VA shunting and no revisions were required. Conclusion.- VA shunting offers satisfactory clinical outcomes in bedridden patients with hydrocephalus and must be considered as an alternative treatment modality for the same group of patients with VP shunt dysfunction.